Economic dominance of resource opportunities of hunting industry in the environmental policy of Ukraine. - Trusova, Natalia; Трусова, Наталя Вікторівна; Vinichenko, Igor; Svynous, Ivan; Yeremenko, Denys; Єременко, Денис Володимирович; Pochernina, Nataliia; Почерніна, Наталя Вікторівна (My University, 2022)
ENG The purpose of this study is the substantiation of the economic dominance of the resource potential of the hunting industry, which is based on a methodical approach to the reproduction of hunting natural resources. A me thodical approach to the reproduction of hunting natural resources with a high level of environmental sustainability of natural capital in order to evaluate the effectiveness of its use in the practical activities of hunting enterprises on the basis of the existing environmental policy of the country, integrated in the space of public-private partnership is justified. Qualitative signs of the economic dominance of the reproduction of hunting natural resources with a high level of environmental sustainability of the natural capital of the hunting industry have been determined. A block di agram of the reproductive process and a matrix of impacts of the hunting industry ecosystem on the resource poten tial of natural capital have been constructed. The toolkit and complex methodology of economic evaluation of the level of environmental sustainability of natural capital in the ecosystem of the hunting industry are substantiated. The economic indicators of the effective development of the hunting industry in Ukraine are analyzed. The method ology for assessing the level of security of the environmental sustainability of the natural capital of the hunting in dustry under the influence of stimulating and disincentive factors is proposed.
Економічна домінанта ресурсних можливостей мисливського господарства в екологічній політиці України.
Keywords: Natural Capital; Hunting Enterprises; Ecosystem; Biomass; Wild Animals; Medicinal Herbs